Tramas territoriais e tessituras multidimensionais em comunidades quilombolas na Paraíba - Fredrich, Maria Salomé Lopes (2018)
In Paraíba, the resistance of the black population to the cruelties of slavery, persecution and mistreatment, in various contexts and in various forms, which have formed territories of resistance and living - such as the quilombos - have recently been recovered with a critical point of view, including the geographical science, in a cultural approach. It is from this perspective that our analysis is based on. We also carried out a study to recover the experience, the meanings, the daily life, the multidimensionality of the networks founded on strategies of mobility and permanence emphasizing how the territories and territorialities of the quilombolas communities in Paraíba are being appropriated. In this sense, we aim to analyse the process of the dynamics and the territorial matters of Pedra D'Água, located in the municipality of Ingá, in the Mesoregion of Agreste Paraibano. We seek to reconstruct historical ancestry and multidimensional references between the territories of Pedra D'Água, Matão, Grilo and Matias. The approach is based on present and local situations, but without neglecting the broader scales. The constructed hypothesis is that the process of resistance of the quilombola communities has been the propeller of the dynamics of the territories and the networks, generating the feeling of belonging to the material and symbolic territory, which is an inducer of territorialities. Thus, the arguments were constructed, fundamentally, in the discussion of territory, network, territoriality and identity, interweaving the corresponding relation between materiality and immateriality of the territory, and authors such as Raffestin (1993), Bonnemaison (2002), Almeida (2005, 2008) ), Haesbaert (2013, 2016), Souza (2003), Almeida and Vargas et al. (2011), Vargas (2015), Marques (2015), Santos (2015), Hall (2011), Rodrigues (2011), Bauman (2005), among others, aid in this interpretation. The transversality constituted the fundamental phase for analysis and results purposes, and we are going through some analytical situations about the resistance practices of quilombola communities, such as: the territoriality of Pedra D'água quilombolas involves, among other things, a network between groups expressing their differentiated identity? Is there a unity of cultural practices and a symbolic universe shared via networks between Pedra D'Água, Matão, Grilo and Matias? The territorialities emanating from the appropriation of the living territory mark the black and quilombola identity in Pedra D 'Água? We conducted the documentary research in the Regional Section of INCRA / PB and in the official portals of the FCP and SEPPIR. We also gathered information in the literature on the subject in Paraíba, as well as the field work in these territories, especially in Pedra D'Água, where it was possible to use the lines of the interlocutors and interlocutors because we understand that this exercise is indispensable in the interpretation of social, cultural and political benchmarks. We conclude that the territorialities arise in the middle of the relationship between remaining in the territory and the mobilities, which in a more abstract perspective, mediated other relations in spatial terms, oriented to interactions and (re) creation of sociabilities and territorialities mediated by the demands and articulations eminently identity, political and resistance.